Pencapaian Hasil Belajar Melalui Peningkatan Kemampuan Mengajar - Daud, Muhammad Nur (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2012)
Highly qualified teachers will be able to conduct better and high quality teaching-learning activities too. Such an ability can be seen when a teacher plan, teach, and assess students’ learning outcomes. Teachers should possess teaching abilities such as ability master subject matters, ability to manage teaching-learning process, ability to manage the classroom, ability to utilize teaching methods/media, ability to manage teaching-learning interactions, and ability to assess students’ learning outcomes. If a teacher possesses those abilities, the students will be motivated to learn. Their motivation will of course translate into increase achievements. As a result, the teaching-learning process will run effectively and efficiently.